Turquoise boy - Cohlene, Terri, 1950-; Reasoner, Charles (Vero Beach, Fla. : Rourke Corp., 1990)
A retelling of a Navajo Indian legend in which Turquoise Boy searches for something that will make the Navajo people's lives easier. Includes a brief history of the Navajo people and their customs.
5.1
5-8
Keywords: Navajo Indians -- Folklore; Navajo Indians -- Social life and customs -- Juvenile literature; Navajo Indians -- Folklore; Navajo Indians -- Social life and customs; Indians of North America -- Social life and customs; Navajo Indians -- Legends; Navajo Indians -- Social life and customs; Native Americans -- Southwestern States -- Social life and customs; Integrated Ed -- Humanities -- Level C2.; Navajo Indians -- Legends; Indians of North America -- Social life and customs